Fabrication of CPW-Fed Fractal Antenna for UWB Applications with Omni-Directional Patterns - Tohid Sedghi; Mahdi Jalali; Tohid Aribi (The Scientific World Journal)
Novel and compact CPW-fed antennas are proposed comprised of a fractal patch and modified ground-plane. The ground-plane is truncated at the center and includes dielectric notches at its side to enhance the antenna’s impedance bandwidth. The dimensions of the notches effectively control the upper and lower band edges of the antenna. The optimized antenna operates across 2.95–12.81 GHz for S11≤-10 dB. Omnidirectional radiation pattern is achieved over the full UWB frequency range. The miniaturized antenna has a total size of 14×18×1 mm3. The characteristics of the proposed antenna are suitable for UWB wireless communication requiring low profile antennas.